Craniosynostoses. A case presentation. - Barbara Aleida García Hernández; Olga Lidia Gutiérrez Chongo; Jesús Vila Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
A case of a three-month female infant who was born in an ectopic and institutional delivery is described. His parents are healthy and came to the consultation office due to an enlargement in the posterior part of the head. Precocious Hyperostosis due to synostoses of the sagittal and diastasis suture of the lambdoidal suture was confirmed in the radiography. It was decide to put the patient under surgical treatment after assessing the case with a neurosurgeon. An early diagnosis and treatment of this non frequent disease are of great importance because it does not permit a presentation of neurological sequelae.